tsRNA-Ala-3–0030 drives ovarian cancer progression by suppressing ZNF70 - Wang, Xinchen; Zhou, Ying; Zhou, Xinhao; Zhang, Bing; Liang, Hongwei; Chen, Youguo (Frontiers in Oncology, 2026)
Globally, ovarian cancer remains a leading cause of gynecologic cancer death. This poor prognosis is primarily attributed to advanced disease at diagnosis, a high propensity for recurrence, and the inadequate therapeutic efficacy of current standard regimens. Emerging evidence has established the functional significance of transfer RNA-derived small RNAs (tsRNAs) in tumor biology. Nevertheless, their exact mechanisms and roles in ovarian cancer pathogenesis are not yet fully understood. Our research was designed to profile tsRNA expression, verify its presence in ovarian cancer tissues and established cell lines, and leverage cellular and animal models to decipher the functional roles and molecular mechanisms of these molecules. Our analysis revealed that tsRNA-Ala-3–0030 is significantly upregulated in ovarian cancer models. Higher expression levels of this tsRNA were associated with enhanced malignant behaviors, including proliferation, migration, and invasion. The suppression of tsRNA-Ala-3–0030 expression attenuated these malignant phenotypes, whereas its overexpression promoted tumor progression in both cellular cultures and xenograft models. Mechanistically, tsRNA-Ala-3–0030 directly targeted the tumor suppressor ZNF70, leading to its downregulation and consequent promotion of ovarian cancer growth and metastasis. Restoration of ZNF70 expression reversed the oncogenic effects of tsRNA-Ala-3-0030, confirming its pivotal role in mediating this pathway. Collectively, our findings reveal tsRNA-Ala-3–0030 as a previously unrecognized oncogenic regulator that promotes ovarian cancer progression through ZNF70 downregulation. This study elucidates a tsRNA-dependent tumorigenic mechanism and positions tsRNA-Ala-3–0030 as a dual-purpose prognostic indicator and therapeutic target, advancing personalized treatment strategies.